(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the role of lipid metabolism in liver dysfunction and its impact on the body. The main causes and consequences of lipid metabolism disorders in non-alcoholic fatty liver disease are highlighted. The results of the study show that lipid metabolism disorders increase inflammatory processes in the liver and lead to the development of fibrosis.